Diastolic Function Impairment in Alcoholics - Fernández-Solà, Joaquim; Nicolás, José-María; Paré, Joan-Carles; Sacanella, Emilio; Fatjó, Francesc; Cofán, Montserrat; Estruch, Ramón (Alcoholism, clinical and experimental research, 2000)
Background: Chronic excessive ethanol consumption exerts a deleterious effect on the myocardium. Although the effects of chronic alcoholism on systolic cardiac function are well known, diastolic involvement has been evaluated only partially. Therefore, we determined the presence of left ventricular diastolic impairment in chronic alcoholics and its relation with simultaneous systolic dysfunction. We also assessed the influence of ethanol consumption in diastolic impairment. Methods: Thirty‐five alcoholics with cardiomyopathy (ejection fraction ≤ 50%) and 77 alcoholics with normal systolic function (ejection fraction > 50%) were evaluated. Assessment of New York Heart Association functional class, history of ethanol intake, technetium‐99m radionuclide angiocardiography, and bidimensional Doppler echocardiography with evaluation of systolic and diastolic left ventricular function were performed. Results: Diastolic function impairment was present in one third of the alcoholics without cardiomyopathy, compared with two thirds of the patients with cardiomyopathy (p < 0.01). A pseudonormalization phenomenon of diastolic function was observed in patients with more advanced systolic dysfunction (ejection fraction < 32%). The deterioration of the diastolic parameters correlated with ethanol consumption, regardless of age (r= 0.44, p < 0.001 for ratio of peak velocity of the transmitral flow in early diastole and peak velocity of atrial contraction flow, with lifetime dose of ethanol). Conclusions: There seems to be a dose‐dependent effect of ethanol on systolic and diastolic heart function. Diastolic function impairment is present in one third of alcoholics with normal systolic function and is even more frequent when systolic dysfunction coexists.